Symptoms of Shortness Breath With Cough and The Incidence of Tuberculosis in Indonesia: Analysis of The 2023 Indonesian Health Survey - Priasmoro, Dian Pitaloka; Asri, Yuni; Jamil, Mokhtar; Maulina, Rifzul (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Tuberculosis (TB) remains a major public health problem, particularly in high-burden countries, where delayed diagnosis contributes to continued transmission. Cough and respiratory symptoms are often the earliest clinical indicators, making them essential for screening and case detection. Objective: This study aimed to analyze the association between cough with shortness of breath and TB diagnosis in Indonesia. Methods: A cross-sectional analysis was conducted using data from 2,435 male and female respondents in the 2023 Indonesia Health Survey. The dependent variable was self-reported TB diagnosis within the past year. Independent variables included age, sex, and occupation. Linear regression was applied with 95% confidence intervals (CI). Results: Of respondents, 41.15% reported TB diagnosis within six months, while 58.85% were diagnosed earlier. Males (60.04%) were more affected. Regression analysis showed a significant association between cough with shortness of breath and TB (Coef. = 0.16; p < 0.001; 95% CI: 0.111–0.208). Conclusion: Cough and respiratory symptoms remain strong predictors of TB, highlighting their importance in early screening and treatment monitoring.